Development of self-forming doxorubicin-loaded polymeric depots as an injectable drug delivery system for liver cancer chemotherapy - Pinunta Nittayacharn (2018)
© 2017, Springer Science+Business Media New York. Abstract: The objective of this work was to develop self-forming doxorubicin-loaded polymeric depots as an injectable drug delivery system for liver cancer chemotherapy and studied the release profiles of doxorubicin (Dox) from different depot formulations. Tri-block copolymers of poly(ε-caprolactone), poly(D,L-lactide) and poly(ethylene glycol) named PLECs were successfully used as a biodegradable material to encapsulate Dox as the injectable local drug delivery system. Depot formation and encapsulation efficiency of these depots were evaluated. Results show that depots could be formed and encapsulate Dox with high drug loading content. For the release study, drug loading content (10, 15 and 20% w/w) and polymer concentration (25, 30, and 35% w/v) were varied. It could be observed that the burst release occurred within 1–2 days and this burst release could be reduced by physical mixing of hydroxypropyl-beta-cyclodextrin (HP-β-CD) into the depot system. The degradation at the surface and cross-section of the depots were examined by Scanning Electron Microscope (SEM). In addition, cytotoxicity of Dox-loaded depots and blank depots were tested against human liver cancer cell lines (HepG2). Dox released from depots significantly exhibited potent cytotoxic effect against HepG2 cell line compared to that of blank depots. Results from this study reveals an important insight in the development of injectable drug delivery system for liver cancer chemotherapy. Graphical Abstract: Schematic diagram of self-forming doxorubicin-loaded polymeric depots as an injectable drug delivery system and in vitro characterizations. (a) Dox-loaded PLEC depots could be formed with more than 90% of sustained-release Dox at 25% polymer concentration and 20% Dox-loading content. The burst release occurred within 1–2 days and could be reduced by physical mixing of hydroxypropyl-beta-cyclodextrin (HP-β-CD) into the depot system. (b) Dox released from depots significantly exhibited potent cytotoxic effect against human liver cancer cell lines (HepG2 cell line) compared to that of blank depots. (c) Dox-loaded depots showed bulk erosion with hollow core at day 60.[InlineMediaObject not available: see fulltext.].